Analisis Kekuatan Flange Valve Akibat Pengaruh Bolt Torque pada Kondisi Pressure dan Temperature Berbeda dengan Metode Finite Element Analysis - Meri Rahmi; Suliono; Delffika Canra; Rachmatullah; Yusuf Nur Rohmat; Dedi Suwandi (Jurnal Teknologi dan Rekayasa Manufaktur, 2020)
Pipe connecting system that is connected with a valve using a flange connection. This aims to make it easier to install or disconnect when needed. This connection system includes pipe connections to fittings, valves, equipment, or other parts which are separate parts of the piping system. The analysis of the flange strength on the 4 inch ball valve ANSI 300 aims to determine and ensure that the flange has strength and is safe at the time of tide due to the influence of the torque bolt. In addition, to ensure the connection does not leak when the fluid is passed. The main combination between internal, axial pressure and thermal loading needs to be considered. Flange strength analysis using Finite Element Analysis (FEA) method with use of Solid works software. The analysis of flange strength uses the method of "Flange as weakest part philosophy", namely the full rating used when the value of a certain pressure-temperature on ASME B16.5 is taken for the Maximum Allowable Working Pressure (MAWP) in the piping system. From the results of the FEA analysis, it was found that the flange on the 4 inch ANSI 300 ball valve meets the requirements according to MAWP at different temperatures and pressures. The value of the safety factor also shows that the flange is safe during the piping work process.